Viscosity of Sumbawa Honey Based on Faxen Correction Factor: Consumer Protection Efforts against Fraud - Moh. Irma Sukarelawan; Yudhiakto Pramudya; Siti Anisatur Rofiqah; Endra Putra Raharja (STKIP Singkawang, 2021)
This study is aimed at determining the viscosity of Sumbawa honey. The sample used was produced by the Apis Dorsata species of honeybees, having three different types of concentrations: 10%, 20% and 30%, respectively. The test sample solution was at a temperature of 23.3 ± 0.5 oC. The viscosity value was determined using the corrected vertical spherical oscillation method. The results of this study identified a tendency for increased viscosity to the concentration of honey solution, which has been determined by extrapolating the equation of the linear regression. The relationship of concentration to true viscosity satisfies the equation y = 0.0199x + 0.0160. Furthermore, the Sumbawa honey viscosity was 2.006 Pa.s.